Copper-Templated Formation of Dihelical Oligothiophene–Phenanthroline Assemblies - Schmid, Sylvia; Wunderlin, Markus; Mena-Osteritz, Elena; Bäuerle, Peter (Organic Materials, 2022)
We report the synthesis and comprehensive characterization of a series of (oligo)thiophene-bridged (bis)phenanthroline ligands. The complexation behavior of the ditopic ligands with Cu(I) was explored by high-resolution ESI mass spectrometry, UV-vis spectroscopy, and electrochemistry. Whereas ligands, in which the phenanthrolines are bridged by smaller (oligo)thiophene units, provided mainly mononuclear complexes, quaterthiophene-based ditopic ligands show a strong tendency to undergo metal-templated self-assembly into double-stranded, dinuclear helicates.
Keywords: oligothiophenes; phenanthrolines; helicates; copper(I) complexation; optoelectronic properties